Body mass index impacts the lipid-lowing effects of statins in patients with type 2 diabetes - Lulu Sun; Zhuo Wang; Bai Wang; Yuxiang Jia; Qidi Zhao; Jingjun Zhao; Xingtao Huang (Frontiers in Cardiovascular Medicine)
BackgroundIndividuals diagnosed with type 2 diabetes mellitus (T2DM) commonly exhibit elevated lipid levels and an increased body mass index (BMI). The impact of BMI on the efficacy of statins in reducing lipid levels among diabetic patients remains uncertain. We aim to evaluate whether BMI will affect the lipid-lowing effects of statins in patients with T2DM.MethodsIn this retrospective analysis, we screened T2DM patients who were prescribed statins and underwent a 1-year outpatient follow-up recorded in the electronic medical record system. Patients were stratified into three groups: normal weight (BMI < 24 kg/m), overweight (24 kg/m2 ≤ BMI < 28 kg/m2), and obese (BMI ≥ 28 kg/m2). Lipid levels were assessed at two time points, and multivariate logistic regression analysis was used to identify factors influencing the reduction of low-density lipoprotein-cholesterol (LDL-C) levels and lipid control achievement.ResultsThis study included 289 patients, with 82 in normal weigh, 143 in overweight, and 64 in obese. Overweight and obese patients were found to be younger than those with normal weight. Over the 1-year follow-up period, lipid levels decreased in all patients, with a significant reduction observed in LDL-C levels. Notably, obese patients experienced the highest reduction in LDL-C levels compared to the normal and overweight groups (normal weight group ΔLDL 0.78 ± 0.95 mmol/L, p < 0.001; overweight group ΔLDL 0.80 ± 0.88 mmol/L, p < 0.001; obese group ΔLDL 1.11 ± 0.82 mmol/L, p < 0.038). Obese patients exhibited a remarkable 42.02% reduction in LDL levels (normal 27.45%, overweight 30.64%). Multivariate logistic regression analysis indicated that achieving lipid control, defined as LDL < 2.6 mmol/L, was more likely in obese patients compared to those with normal weight [odds ratio [OR] 3.48, 95% confidence interval [CI]: 1.18, 10.21, p = 0.023].ConclusionsThe effectiveness of statins in lowering lipid levels appears to be influenced by the patient's BMI in patients with T2DM. T2DM patients with high BMI may derive greater benefits, particularly in LDL reduction, from statin therapy.